Criminal Law Perspectives on Bribery Cases of Football Scoring - Vicki Dwi Purnomo; Edi Prianto; Noval Maulana Hazzar (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
Football is a very popular sport in the world and even in Indonesia. The population of Indonesia, which is around 365 million, prefers This soccer sport compared to other sports. With such a large potential resource many are interested in making football a media or intermediary for various Messages and information, ranging from its role as a business medium to a political medium. Method This writing research is normative empirical, which is legal research on the application or implementation of normative legal provisions in action in every legal event certain that occurs in society. The main motive related to the setting of scores is money. Gambling syndicates with big capital dare to make a scenario related to the result of a match because They have a lot of money to play at many points. But it must be understood that as long as it does not meet certain elements that are regulated in a criminal manner The score cannot be included in the crime/criminal category but still injures Fair play. Three elements of the legal system, theory from Lawrence M. Friedman is a factor that affects law enforcement, namely the structural component, substance component, and Culture component or legal culture. Law enforcers must be proactive in doing law enforcement of match-fixing because in essence the score arrangement or Bribery in the Speak Ball match is a general offense.